What are the Challenges in Designing An Effective Personal Income Tax System? - Raeni, Raeni (Economics and Finance in Indonesia, 2016)
This article aims to examine the challenges of designing individual's income tax systems in general and particularly to observe taxpayers behaviour in developing countries. This study used case study approach to gain in depth understanding type of taxpayers attitude towards personal income tax systems. Based on the analyses, tax behaviour, which comprises the perception of fairness and motivation to comply, attracts urgent challenges in designing effective tax on personal income in every country and mainly underdeveloped countries. Every human being in each country has their social pattern towards tax policy. When the individual perception of fairness is significant, it will harmonise the client and service approach between taxpayers and governments. This condition would influence tax morale of individuals to comply with the policy and achieve high compliance rate. Therefore, it has argued that personal view of fairness and their motivation to comply with tax systems are becoming vital challenges in designing the tax policy on individual income.